Characterization and role of the selected microbiome in water remediation and gut health of aquacultured marron (Cherax cainii, Austin 2002) - Foysal, Md Javed (Curtin University, 2021)
Seven trials were conducted under laboratory conditions to characterize the gut and rearing water microbiota of marron when exposed to various substrates and fed selected probiotics and non-fishmeal protein sources. The results showed that Lactobacillus spp., and substrate Water Cleanser significantly improved the gut microbial diversity and immune-competence of marron. Non-fishmeal protein ingredients including poultry-by-product and black soldier fly meal have an ability to replace fishmeal protein from marron diet without any detrimental effects.